2022
DOI: 10.5114/aic.2022.118527
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FFR, iFR, and QFR assessment in patients with severe aortic stenosis and coronary heart disease

Abstract: Introduction: Some patients with coronary heart disease are diagnosed with severe aortic stenosis. For further treatment, coronary angiography is performed in these patients. For intermediate lesions, obtaining coronary artery physiological data can facilitate clinical decision-making regarding revascularization.Aim: The study compared the physiological significance of coronary artery stenosis using the fractional flow reserve (FFR) method with instantaneous wave-free pressure ratio (iFR) and quantitative flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As a new non-invasive physiological evaluation index, QFR has many advantages such as fast calculation time and no use of drugs (adenosine). In addition to this, recent studies have reported that QFR also has good diagnostic efficacy in patients with coronary artery disease combined with severe aortic stenosis (AS), superior to the resting distal to aortic coronary pressure (Pd/Pa) ratio and instantaneous wave-free pressure ratio (iFR), when using FFR as a reference ( 37 , 38 ). This technology has been continuously upgraded and improved, with AI techniques being added to the latest QFR ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a new non-invasive physiological evaluation index, QFR has many advantages such as fast calculation time and no use of drugs (adenosine). In addition to this, recent studies have reported that QFR also has good diagnostic efficacy in patients with coronary artery disease combined with severe aortic stenosis (AS), superior to the resting distal to aortic coronary pressure (Pd/Pa) ratio and instantaneous wave-free pressure ratio (iFR), when using FFR as a reference ( 37 , 38 ). This technology has been continuously upgraded and improved, with AI techniques being added to the latest QFR ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Very often, bicuspid valves have more oval orifices, and the self-expandable valve assumes a more oval shape after implantation. This, in turn, may result in PVL and/or make the retrieval of the delivery system difficult after implantation [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical characteristics and risk factors of patients undergoing physiological assessment of borderline coronary stenosis varied significantly by age. Refining the definition of borderline lesions to include not only angiographic findings but also age, gender, and other clinical factors [25] may improve the ability to identify patients who would benefit from physiological assessment and coronary revascularization. However, this promising approach, supported by the existing literature [26,27], warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%